2018
DOI: 10.1016/j.oret.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative OCT-assisted Surgery for Proliferative Diabetic Retinopathy in the DISCOVER Study

Abstract: The results suggest that iOCT is feasible during complex vitreoretinal surgeries in patients with PDR using a microscope-integrated OCT platform. Utilizing intraoperative OCT, appears to frequently offer key information that may impact surgical decision-making and potentially patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Other studies reporting on the impact of iOCT on clinical decision making report similar results as the PIONEER and DISCOVER study [8,14,[22][23][24][25]. The results of these studies suggest that the iOCT fills the gaps in surgical information and these insights may improve quality of care and surgical efficiency.…”
Section: Impact Of Intraoperative Oct On Clinical Decision Makingsupporting
confidence: 60%
“…Other studies reporting on the impact of iOCT on clinical decision making report similar results as the PIONEER and DISCOVER study [8,14,[22][23][24][25]. The results of these studies suggest that the iOCT fills the gaps in surgical information and these insights may improve quality of care and surgical efficiency.…”
Section: Impact Of Intraoperative Oct On Clinical Decision Makingsupporting
confidence: 60%
“…Additionally, in the case of vitreous haemorrhage (which precludes pre-operative OCT macula evaluation), MI-OCT detected ERM, vitreomacular traction, or macular oedema, helping the surgeon to decide whether to treat them simultaneously or later. Moreover, MI-OCT has been used to confirm complete ERM removal in the case of vitreoschisis and differentiate retinal detachment and retinoschisis [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…For posterior segment surgery, iOCT appears to be particularly useful during membrane assessment, such as in PDR and ERM surgery. 25, 26 A recent prospective study utilizing microscope-integrated iOCT during membrane peeling procedures confirmed the ability of the technology to enhance visualization of the underlying membranes and subtle post-peel architecture changes. 15 An additional study recently reported membrane peeling with iOCT feedback was able to performed without the use of adjuvant dyes through the identification of membrane edges with the OCT system.…”
Section: Discussionmentioning
confidence: 82%